Co-Precipitated and Collocated Carbides and Cu-Rich Precipitates in a Fe–Cu Steel Characterized by Atom-Probe Tomography. (December 2014) - Kolli, R. Prakash; Seidman, David N.
Abstract The composition of co-precipitated and collocated NbC carbide precipitates, Fe3C iron carbide (cementite), and Cu-rich precipitates are studied experimentally by atom-probe tomography (APT). The Cu-rich precipitates located at a grain boundary (GB) are also studied. The APT results for the carbides are supplemented with computational thermodynamics predictions of composition at thermodynamic equilibrium. Two types of NbC carbide precipitates are distinguished based on their stoichiometric ratio and size. The Cu-rich precipitates at the periphery of the iron carbide and at the GB are larger than those distributed in the α-Fe (body-centered cubic) matrix, which is attributed to short-circuit diffusion of Cu along the GB. Manganese segregation is not observed at the heterophase interfaces of the Cu-rich precipitates that are located at the periphery of the iron carbide or at the GB, which is unlike those located at the edge of the NbC carbide precipitates or distributed in the α-Fe matrix. This suggests the presence of two populations of NiAl-type (B2 structure) phases at the heterophase interfaces in multicomponent Fe–Cu steels.